2011
DOI: 10.1007/s12328-011-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of eosinophilic esophagitis with atypical clinical course

Abstract: Eosinophilic esophagitis is a rare chronic disease that mainly occurs in middle-aged males. Treatment with a glucocorticoid and/or proton pump inhibitor is usually necessary to relieve unpleasant symptoms. An 83-year-old female patient with dysphagia and heartburn was diagnosed with eosinophilic esophagitis based on endoscopic findings, while histological examination identified dense infiltration of intraepithelial eosinophils. The symptoms and eosinophil infiltration spontaneously disappeared without any trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In Japan, the first EoE case was reported by Furuta et al . in 2006, and since then the cases have been reported increasingly . Likewise, the number of case reports regarding EoE in other Asian countries has been gradually increasing from 2009 .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the first EoE case was reported by Furuta et al . in 2006, and since then the cases have been reported increasingly . Likewise, the number of case reports regarding EoE in other Asian countries has been gradually increasing from 2009 .…”
Section: Epidemiologymentioning
confidence: 99%
“…[23][24][25] In Japan, the first EoE case was reported by Furuta et al 7 in 2006, and since then the cases have been reported increasingly. 26,27 Likewise, the number of case reports regarding EoE in other Asian countries has been gradually increasing from 2009. 8,10,11,13 To date, nine epidemiological studies have been conducted in Asian countries ( Table 1).…”
Section: Epidemiologymentioning
confidence: 99%